2017
DOI: 10.1186/s12916-017-0947-9
|View full text |Cite
|
Sign up to set email alerts
|

Spot sputum samples are at least as good as early morning samples for identifying Mycobacterium tuberculosis

Abstract: BackgroundThe use of early morning sputum samples (EMS) to diagnose tuberculosis (TB) can result in treatment delay given the need for the patient to return to the clinic with the EMS, increasing the chance of patients being lost during their diagnostic workup. However, there is little evidence to support the superiority of EMS over spot sputum samples. In this new analysis of the REMoxTB study, we compare the diagnostic accuracy of EMS with spot samples for identifying Mycobacterium tuberculosis pre- and post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Another study conducted in Uganda in 2017 by Michael E concluded that spot sample is as good as early morning sputum samples for TB diagnosis. This study also concluded that there is no yielding difference between spot and morning collection methods for diagnosis of TB using Gene Xpert MTB/RIF Assay (Michael et al, 2017).…”
Section: Discussionmentioning
confidence: 65%
“…Another study conducted in Uganda in 2017 by Michael E concluded that spot sample is as good as early morning sputum samples for TB diagnosis. This study also concluded that there is no yielding difference between spot and morning collection methods for diagnosis of TB using Gene Xpert MTB/RIF Assay (Michael et al, 2017).…”
Section: Discussionmentioning
confidence: 65%
“…As mentioned by laboratory professionals, the current sputum collection method (spotspot) has been leading them to Health system diagnosis delay. The different studies' findings, including systematic review and meta-analysis, were against this finding [18][19][20]. Early morning sputum samples (EMS) are generally considered to yield a greater number of positive results than spot samples and to have higher sensitivity and specificity for culture, yet the published data to support this assumption is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…showed that spot sample are similar with early morning sputum sample for diagnosis of Pulmonary TB. [18] There is delay in health-seeking behaviors for various diseases and which is also true for pulmonary TB. TB patients at times have to make multiple visits to health facilities before they were diagnosed and get treated.…”
Section: Discussionmentioning
confidence: 99%